Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Black soldier fly larvae promote the resource of cyanobacteria: Frass-mixed compost - Rui Li; YuFeng Jiang; ChangXue Wang; Kai Luo; XiaoLei Fan; TianHui Lin; RongBo Guo; ShanFei Fu (Journal of Environmental Chemical Engineering, 2024)

Highly stable zinc anodes enabled by a dual-function additive of in-situ film formation and electrostatic shielding - Rui-han Ji; Hao Fu; Qing Wen; Pei-Yao Li; Pei Yang; Yu-Jing Chen; He-zhang Chen; Jia-feng Zhang; Ling-jun Li; Jie-xi Wang; Qing Wu; Xia-hui Zhang; et al. (Chemical Engineering Journal, 2024)

Integrative experimental and computational analysis of the impact of KGM's polymerization degree on wheat starch's pasting and retrogradation characteristics - Yi Zhao; Juan Wang; Rui He; Yuanyuan Ren; Jin Fu; Yunjun Zeng; Kangyi Zhang; Geng Zhong (Carbohydrate Polymers, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Z-Ligustilide restricts rabies virus replication by inducing ferroptosis through the ACSL4-LPCAT3-POR pathway - Jianqing Zhao; Qianruo Wang; Zhenkun Liu; Meixin Sun; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Estimating epidemic trajectories of SARS-CoV-2 and influenza A virus based on wastewater monitoring and a novel machine learning algorithm - Songzhe Fu; Yixiang Zhang; Yinghui Li; Ziqiang Zhang; Chen Du; Rui Wang; Yuejing Peng; Zhijiao Yue; Zheng Xu; Qinghua Hu (Science of The Total Environment, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Stubble height and irrigation significantly influenced the carbon footprint of ratoon rice cropping system in South China - Xiangyu Hu; Youqiang Fu; Nanxun Huang; Xinyu Wang; Rui Hu; Xuhua Zhong; Junfeng Pan; Meijuan Li; Yanzhuo Liu; Qunhuan Ye; Yuanhong Yin; Kaiming Liang (Field Crops Research, 2024)

Comprehensive investigation of daytime radiative cooling technology for sustainable grain storage: A combined approach of field measurement and CFD simulations - Chongjia Lin; Yunlong Wang; Zhihang Zhao; Xisheng Lin; Rui Li; Zhaoping Zheng; Xuhua Shen; Zhongqing Lang; Weizhi Zhou; Jinbei Wang; Dan Yuan; Yankai Sun; et al. (Building and Environment, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Efficient degradation of Rhodamine B by visible-light-driven biomimetic Fe(III) complex/peroxymonosulfate system: The key role of FeV=O - Chen-Xuan Li; Rui Wang; Wen Sun; Kangping Cui; Xian-Zhong Fu; Minshu Cui; Yihan Chen; Zhi Guo; Yingying Liu (Journal of Environmental Chemical Engineering, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

“Fast-charging” mechanism of Li3VO4 from the perspective of material science for lithium-ion battery - Rui Wang; Yuan Li; Gaoyang Li; Yihan Fu; Youzhi Wu; Fen Ran (Chemical Engineering Journal, 2024)

Incorporating hydrogen bonding networks in microporous polymer membranes for high-flux hydrocarbon separation - Yanxiong Ren; Jingqi Fu; Rui Ding; Yunshu Li; Xu Liang; Zheyuan Guo; Jianyu Wang; Ziting Zhu; Hong Wu; Guangwei He; Zhongyi Jiang (Chemical Engineering Journal, 2024)

QTL mapping and omics analysis to identify genes controlling kernel dehydration in maize - Xining Jin; Xiaoxiang Zhang; Pingxi Wang; Juan Liu; Huaisheng Zhang; Xiangyuan Wu; Rui Song; Zhiyuan Fu; Shilin Chen (Theoretical and Applied Genetics, 2024)

A data-driven computational framework for non-intrusive reduced-order modelling of turbulent flows passing around bridge piers - Chuanhua Zhu; Dunhui Xiao; Jinlong Fu; Yuntian Feng; Rui Fu; Jinsheng Wang (Ocean Engineering, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Dynamics changes in metabolites and pancreatic lipase inhibitory ability of instant dark tea during liquid-state fermentation by Aspergillus niger - Haoran Sun; Ranqin Fan; Rui Fang; Shanshan Shen; Yu Wang; Jialin Fu; Rui Hou; Runchen Sun; Shinuo Bao; Qi Chen; Pengxiang Yue; Xueling Gao (Food Chemistry, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Wastewater surveillance together with metaviromic data revealed the unusual resurgence of infectious diseases after the first wave of the COVID-19 outbreak - Ziqiang Zhang; Fenglan He; Liu Yi; Zhiqiang Deng; Rui Wang; Lixin Shen; Songzhe Fu (Journal of Hazardous Materials, 2024)

Activating the synergistic effect in Ni-Co bimetallic MOF for enhanced plasma-assisted ammonia synthesis - Yuhang Jing; Feng Gong; Sijun Wang; Wenbin Wang; Peng Yang; Enkang Fu; Rui Xiao (Fuel, 2024)

Effect of Licorice on Gene Expression Related to the Growth of Asian Seabass Lates calcarifer - Rui Yang; Wang Zhao; Yifu Wang; Zhengyi Fu; Jing Hu; Shengjie Zhou; Minghao Li; Zhenhua Ma (Journal of Marine Science and Engineering, 2024)
The Asian seabass (Lates calcarifer) has high economic value and is the primary aquaculture species in China. Licorice (Glycyrrhiza uralensis) as a feed additive has demonstrated significant immunological benefits in aquaculture. However, its effects on the growth of aquatic animals are largely unexplored. This study explored the influence of licorice on the level of growth-related genes in Asian seabass by conducting an experiment using artificial feed with 0%, 1%, 3%, and 5% licorice. The impact on growth performance and the expression of several genes, including growth hormone–releasing hormone (GHRH), growth hormone (GH), growth hormone receptor (GHR), insulin-like growth factor 1 (IGF1), IGF2, IGF2 receptor (IGF2R), myostatin 1 (MSTN1), and myostatin 2 (MSTN2), were studied over 56 d. According to the results, the 3% and 5% licorice-supplemented diets significantly improved survival rates and weight gain compared to the control group. Licorice affected the level of growth-associated genes in Asian seabass and significantly increased the levels of GHR and IGF1 in the liver. However, a 5% licorice diet downregulated the expression of IGF2. As the licorice content in the diet increased, the levels of IGF2R and MSTN1 in the muscle tissue first decreased and then increased, and licorice addition inhibited the MSTN2 expression. The inclusion of licorice in the feed led to a significant downregulation of the GH and GHRH expression (p

Antioxidant and Metabolic Response to Acute Acidification Stress of Juvenile Yellowfin Tuna (Thunnus albacares) - Xiaoyan Wang; Rui Yang; Zhengyi Fu; Lei Zhao; Zhenhua Ma (Journal of Marine Science and Engineering, 2024)
This study aimed to explore the impact of acute acidification on the antioxidant, metabolic performance, and liver histology of juvenile yellowfin tuna. The experiment subjected juvenile yellowfin tuna to a pH gradient environment of 8.1, 7.6, 7.1, and 6.6 for 48 h. The findings indicate that a seawater pH of 7.1 significantly impacts the antioxidant and metabolic systems of the juvenile yellowfin tuna in comparison to the control group. At pH 7.1, there were observed increases in glutathione reductase (GR), total antioxidant capacity (T-AOC), lactate dehydrogenase (LDH), hexokinase (HK), pyruvate kinase (PK), sodium-potassium ATPase (Na+K+-ATP), and calcium-magnesium ATPase (Ca2+Mg2+-ATP). Conversely, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TGs) were not significantly different across the treatment groups. However, an increase in transaminases at pH 7.1 suggested potential liver damage, which was further supported by observed structural liver tissue degeneration and hepatocyte vacuolation. In conclusion, under conditions of acute acidification stress, there is a decrease in antioxidant capacity and a suppression of metabolic levels in juvenile yellowfin tuna, leading to oxidative damage. This study lays the foundation for an in-depth understanding of the response mechanisms of juvenile yellowfin tuna in response to seawater acidification as well as healthy tuna farming in the broader context of seawater acidification.

Optimizing grape growth, berry quality and phenolic compounds with foliar co-application of iron and calcium - Yaqi Wang; Huiling Ma; Xiaoke Fu; Haoyu Wang; Rui Wang (South African Journal of Botany, 2024)

The boom era of emerging contaminants: A review of remediating agricultural soils by biochar - Renjie Hou; Jian Zhang; Qiang Fu; Tianxiao Li; Shijun Gao; Rui Wang; Shan Zhao; Bingyu Zhu (Science of The Total Environment, 2024)

Sustainable treatment of aquaculture water employing fungi-microalgae consortium: Nutrients removal enhancement, bacterial communities optimization, emerging contaminants elimination, and mechanism analysis - Rui Mi; Xuda Wang; Ying Dong; Shilei Li; Zelong Zhao; Xiaoyan Guan; Jingwei Jiang; Shan Gao; Zhiyu Fu; Zunchun Zhou (Science of The Total Environment, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Effect of nano zero-valent iron on the anaerobic digestion of food waste: Performance and mechanism - Ruonan Wang; Naif Abdullah Al-Dhabi; Yufeng Jiang; Xiaofeng Dai; Rui Li; Wangwang Tang; Rongbo Guo; Shanfei Fu (Fuel, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

The Photoperiod Significantly Influences the Growth Rate, Digestive Efficiency, Immune Response, and Antioxidant Activities in the Juvenile Scalloped Spiny Lobster (Panulirus homarus) - Yinggang Wang; Rui Yang; Zhengyi Fu; Zhenhua Ma; Zemin Bai (Journal of Marine Science and Engineering, 2024)
This study aimed to elucidate the effects of different photoperiods (0 L:24 D, 6 L:18 D, 12 L:12 D, 18 L:6 D, 24 L:0 D, “Light (L) and Dark (D)”) on the growth performance and physiological responses of the juvenile scalloped spiny lobster (Panulirus homarus). Over a period of 56 days, parameters such as growth rate, digestive enzyme, immune enzyme, and antioxidant enzyme were meticulously evaluated in 90 lobsters subjected to these varying light conditions. The present study found no significant differences in survival rate (SR), molting frequency (MF), and meat yield production (MYP) among the various photoperiod treatments (p > 0.05). Notably, the highest weight gain rate (WGR) and specific growth rate (SGR) were observed under a 12 L:12 D photoperiod. In the continuous dark phase (0 L:24 D), pepsin (PEP) activity remained high in gastric tissues, while trypsin (TRYP) and chymotrypsin (CHT) activities reached the highest in hepatopancreas tissues. The α-amylase (AMS) activity in the hepatopancreas was most elevated under 18 L:6 D, and the optimal lipase (LPS) activity was recorded under 12 L:12 D. The activity of acid phosphatase (ACP) in the hepatopancreas was highest in the absence of light (0 L:24 D), whereas the activities of alkaline phosphatase (AKP) and lysozyme (LZM) were most effective under the 12 L:12 D photoperiod. The total antioxidant capacity (T-AOC), along with catalase (CAT) and superoxide dismutase (SOD) activities of the hepatopancreas reached the highest at 12 L:12 D. The highest activity of glutathione peroxidase (GSH-Px) was seen under 18 L:6 D. The concentration of malondialdehyde (MDA), a marker of oxidative stress, was found to be highest under 12 L:12 D. Consequently, this specific photoperiod is essential for achieving optimal growth and maintaining appropriate physiological balance in the scalloped spiny lobster during aquaculture. These findings provide a foundational guideline for establishing the lighting environment in the farming of the juvenile scalloped spiny lobster.

Deep learning in water protection of resources, environment, and ecology: achievement and challenges - Xiaohua Fu; Jie Jiang; Xie Wu; Lei Huang; Rui Han; Kun Li; Chang Liu; Kallol Roy; Jianyu Chen; Nesma Talaat Abbas Mahmoud; Zhenxing Wang (Environmental Science and Pollution Research, 2024)

Monitoring and prediction of Aeromonas veronii dynamics via absolute quantification microbiome sequencing facilitated the development of a risk assessment tool in a shrimp farm - Wenyu Zhao; Rui Wang; Yixiang Zhang; Qian Zhang; Songzhe Fu (Aquaculture, 2024)

Regional background ozone estimation for China through data fusion of observation and simulation - Zhixu Sun; Jiani Tan; Fangting Wang; Rui Li; Xinxin Zhang; Jiaqiang Liao; Yangjun Wang; Ling Huang; Kun Zhang; Joshua S. Fu; Li Li (Science of The Total Environment, 2024)

Targeted amplicon sequencing facilitated a novel risk assessment framework for assessing the prevalence of broad spectrum bacterial and coronavirus diseases - Songzhe Fu; Haifeng Li; Fenglan He; Rui Wang; Yixiang Zhang; Ziqiang Zhang; Hui Li (Science of The Total Environment, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Dispersion of sandy sediments during marine–continental transition: An integrated study from the Late Paleozoic western Ordos Basin - Zhiwei Wang; Lei Liu; Jianling Hu; Feng Wang; Dan Li; Jingqi Zhang; Shuyue Zhu; Rui Zhang; Fei Zhao; Chenggong Zhang; Siyi Fu; Hongde Chen (Marine and Petroleum Geology, 2024)

Reducing infertile eggs and dead embryos during egg hatching based on respiration - Jiaojiao Wang; Rui Cao; Qiaohua Wang; Meihu Ma; Dandan Fu (Journal of Cleaner Production, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

RETRACTED: Elucidating the mechanisms of rapid O3 increase in North China Plain during COVID-19 lockdown period - Rui Li; Yining Gao; Yu Han; Yi Zhang; Baojun Zhang; Hongbo Fu; Gehui Wang (Science of The Total Environment, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)